Inequality and employment sensitivities to the falling labour share - Marika Karanassou; Hector Sala (Queen Mary University of London, School of Economics and Finance, 2011)
This paper aims at identifying the labour share (wage-productivity gap) as a major factor in the evolution of inequality and employment. To this end, we use annual data for the US, UK and Sweden over the past forty years and estimate country-specific systems of labour demand and Gini coefficient equations. Further to the statistical significance of our models, we validate their economic significance through counterfactual simulations. In particular, we evaluate the contributions of the labour share to the trajectories of inequality and employment during specific time intervals in the post-1990 years. We find that during the nineties the cost of a one percent increase in employment was in the range of 0.7%-0.9% higher inequality in all three countries. However, in the 2000s, whereas the inequality-employment sensitivity ratio slightly fell in the US, it exceeded unity in the countries on the other side of the Atlantic. It obtained its highest value in the UK, where a 1% growth in employment was achieved at the expense of 1.3% worsening in income inequality. In the light of the significant influence of the time-varying labour share on the inequality and employment time paths documented in our sample, the evolution of the wage-productivity gap deserves the attention of policy makers.
Keywords: D30; E25; E24; 330; income inequality; labour income share; employment; Lohnquote; Einkommensverteilung; Beschäftigung; Schätzung; USA; Großbritannien; Schweden